Proposed Corporate Performance Management Using Knowledge-Based Performance Management System (KBPMS) For Privy - Dimas Kusuma, Vieri (Journal of Economics and Business UBS, 2024)
PT. Privy Identitas Digital or Privy Digital Identity (Privy) is a firm established in Jakarta in 2016 that specializes in the provision of Certified Electronic Certificate Organization and Electronic Signature Organization services. Privy offers legally enforceable digital signature services, along with reliable digital identities, facilitating direct connections between businesses and customers. This thesis investigates the deployment of an integrated performance management system emphasising the Knowledge-Based Performance Management System (KBPMS) at PT. Privy Identitas Digital (Privy), a firm that specialises in certified electronic certificates and digital signatures. The exponential expansion of Privy's services has highlighted the need of aligning its business strategy with frontline operations by using integrated planning and monitoring tools. The research study of integrated performance management, which includes financial goals, customer, process, and employee perspectives, is examined in detail. The suggested method uses a robust performance management framework to address enterprise issues including traditional marketing tactics and the absence of Key Performance Indicators (KPIs). KBPMS optimises company performance, meets business objectives, and promotes continuous development. Significant benefits are anticipated to result from the implementation of the KBPMS, including the following: increased talent development by means of targeted training and feedback derived from individual performance evaluations; enhanced employee engagement and motivation through transparent feedback and aligned goals; increased organisational agility and responsiveness to market changes via data-driven performance insights; and optimised resource allocation and cost reduction via the KBPMS. By showcasing the advantages of incorporating digital technology into performance management, it facilitates the adoption of comparable approaches by other organisations, thereby maximising the capabilities of their workforce.